Analisa Dampak Sistem Rotasi Mutasi Promosi Terhadap Kinerja Karyawan (Studi Kasus pada PT Pupuk Kujang) - Indry Aulia Rahmawati; Enjang Suherman (Jurnal Ekonomi dan Bisnis Digital, 2024)
The promotion transfer rotation system is an approach to human resource management that uses employee shifts between positions, between locations, or organizational units, and provides promotions based on performance and potential. The purpose of this research is to analyze the impact of the promotion mutation rotation system on employee performance. Three sources were selected using purposive sampling according to the research criteria. Researchers use qualitative data types consisting of primary data, namely direct data collected by researchers from sources through interviews and secondary data through interview documentation, company reports and literature studies. The results of the interviews were made into a table as a presentation of the data obtained with conclusions regarding the impact of the mutation rotation system at PT Pupuk Kujang. According to the interviewees, rotation helps develop cross-functional skills, transfers support diversification of experience, and promotions provide recognition for achievements. The main goal of an RMP system is to develop employee skills, make optimal use of internal talent, and meet organizational needs in an effective manner.